On the bus and online: instantiating an interactive learning environment through design-based research. Issue 5 (4th July 2017) - Kartoglu, Ümit; Vesper, James L.; Reeves, Thomas C.
ABSTRACT: The World Health Organization converted an award-winning experiential learning course that takes place on a bus traveling down the "cold chain" for time- and temperature-sensitive pharmaceutical products in Turkey to an online interactive learning environment through design-based research. Similarities and differences in the objectives of the two courses as well as the overlap in the learning activities, tools, and technologies deployed in courses are delineated. Many learning activities from the real bus course were successfully moved to the online course, but a few learning activities from the bus course could not be replicated in the online environment. However, several new and arguably more effective learning activities were implemented online that could not be accomplished on the bus. Design principles for developing online experiential learning environments were derived from the design-based research.